PERBANDINGAN VARIASI SUHU DAN KANDUNGAN LOGAM BAHAN KERAMIK DENGAN BAHAN LOGAM SEBAGAI KETEL RICE COOKER - Agung Purnomo; Rizal Aditya; Denny Darmawan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research was aimed to know comparison of temperature variation and metal content in ceramic material and metal material which be used to rice cooker pan. Measuring method of temperature which be used is measuring voltage change of LM 35 which be converted to temperature unit. Measuring method of metal content which be used is using atomic absorption spectroscopy which focus in content of Cu, Cd and Al. Result of variation temperature research shows ceramic pan has homogeneous temperature variation and progressive temperature increase. Besides metal pan has non homogeneous temperature variation and extreme temperature increase. Result of metal contents research shows Cu, Cd and Al content in the ceramic pan are lower than in the metal pan. It shows that the ceramic pan is better to be used for rice cooker pan. Keywords: Rice cooker, Pan, Ceramic, Metal, Temperature.